Pembentukan Usahawan Kraf Tangan Wanita di Malaysia: Peranan Sikap, Warisan Keluarga dan Pembudayaan Nilai Agama - Nor Hanim Awang @ Mohd Noor; Norfatiha Othman; Nor Hayati Sa'at (Kajian Malaysia, 2021)
The participation of women in entrepreneurship plays a significant role in economic development especially in reducing unemployment, increasing production and consumption, achieving gender equality, social and cultural reforms. One of the dominant areas for women is batik and songket entrepreneurs who are synonymous with women on the East Coast of Peninsular Malaysia. Studies have identified three key elements that contribute to the development of this craft entrepreneur, viz. attitude, business inheritance and religious value culture. Qualitative design methods based on case studies and in-depth interviews were used in this study on 12 informants in the state of Kelantan and Terengganu in Malaysia. The findings show that there are three main factors that cause the formation of women handicraft entrepreneurs, namely attitude, family heritage and religious values. Hence, all the factors that make up a female handicraft entrepreneur in Malaysia are discussed in this article. The findings imply that increasing women entrepreneurs in handicrafts can raise the quality of handicraft products into becoming the best tourism products in the East Coast.